Imunidade de aves (Gallus gallus) para Salmonella enterica subesp. enterica Sorovar Gallinarum biovar Gallinarum - Acelas Díaz, Silvia Juliana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The fowl typhoid is a systemic disease of chickens caused by Salmonella enteric subsp. enteric serovar Gallinarum biovar Gallinarum. This bacterium is highly pathogenic for chickens at any age, causing mortality even in adult birds. The progress of clinical signs differs among different lines of chickens. White lines of chickens are considered resistant and hardly mortality is observed. Chickens of brown lines are more susceptible and develop severe clinical signs with high mortality rates. The aim of this study was to evaluate the development of the disease and γδ T cells influx during the infection with SG in different varieties of layer-hens. In this study, 50 commercial layer-hens of white lines were used and 60 commercial layer-hens of brown lines were divided into 4 groups: group A (control for white layers), group B (infected white layers), group C (control for brown layers) and group D (infected brown layers). Chickens in groups B and D were challenged at 30 days-old with SG. At 6 hours post-infection (6 hpi) and 1, 3 and 5 days post-infection (dpi), three hens per group were sacrificed for sampling. The population of γδ T cells was evaluated by immunohistochemistry in caecal tonsils and liver; cytokines were quantified by real time RT-qPCR in caecal tonsils and spleen and samples of serum were used for biochemistry analysis. The macroscopic lesions were more intense in the hens of group D, at 3 dpi, in comparation with the group B. The bacterial numbers in spleen and liver from chickens in the group D were higher at 3 and 5 dpi. After 6 dpi, the mortality caused by fowl typhoid, began in group D. Differently, group B had no mortality. The group B had higher amounts of the proteins ceruloplasmin, albumin and α1- acid glycoprotein, in comparation to group D, but did not show statistical difference (p>0.05). The protein levels PM=99.000 Da, PM=90.000 Da and transferrin were significantly higher in group B (p<0.05) at ...

O tifo aviário é uma doença sistêmica causada por Salmonella enterica subesp. enterica sorovar Gallinarum biovar Gallinarum (SG). Esta bactéria é altamente patogênica para aves em qualquer idade, causando mortalidade inclusive em aves adultas. No entanto, a progressão dos sinais clínicos em galinhas pode diferir entre as diferentes variedades de aves. Aves de variedade branca são consideradas mais resistentes e dificilmente se observa mortalidade. Aves de variedade vermelha são suscetíveis e desenvolvem quadros clínicos mais severos com altas taxas de mortalidade. O objetivo do presente estudo foi avaliar o desenvolvimento da doença e infiltrado de linfócitos T γδ durante a infecção por SG em diferentes variedades de aves. Neste trabalho, utilizaram-se 50 aves comerciais para postura de variedade branca e 60 aves comerciais para postura de variedade vermelha que foram distribuídas em quatro grupos: grupo A (controle de aves brancas), grupo B (aves brancas infectadas), grupo C (controle de aves vermelhas) e grupo D (aves vermelhas infectadas). As aves dos grupos B e D foram desafiadas aos 30 dias de vida com SG. Às 6 horas pós-infecção (6 hpi) e 1, 3 e 5 dias pós-infecção (dpi), três aves/grupo foram eutanasiadas para amostragem. A população de linfócitos T γδ foi avaliada por imuno-histoquímica em tonsilas cecais e fígado; citocinas foram quantificadas por RT-qPCR em tempo real em tonsilas cecais e baço e amostras de sangue para análises bioquímicas séricas. As lesões macroscópicas foram mais intensas nas aves do grupo D, a partir do 3º dpi, em comparação com as aves do grupo B. As contagens bacterianas no baço e fígado tiveram maiores quantidades nas aves do grupo D no 3° e 5° dpi. Após o 6° dpi, as aves do grupo D começaram a sucumbir ao tifo aviário, diferente das aves do grupo B, que não apresentaram nenhuma mortalidade. Aves do grupo B tiveram maiores quantidades das proteínas ...
Keywords: Ave; Ave - Doenças; Resposta imune; Salmonella gallinarum; Imunidade celular; Immune response